The Vietnamese version of the Home Falls and Accidents Screening Tool (HOME FAST) - A preliminary study of validity and inter-rater reliability - Mackenzie, Lynette; Le, Van Thanh; Nguyen, Doan Mai Ngoc; Dao, Thy Hoang Phuong (Frontiers in Public Health, 2023)
Introduction: The Vietnamese Home Falls and Accidents Screening Tool (HOME FAST) was developed to measure the number of home hazards present in the homes of older Vietnamese people and the risk of falls. Methods: The HOME FAST and the HOME FAST manual were translated into Vietnamese by an independent translator and underwent backward translation by local health professionals into English to evaluate the accuracy of the translation. A panel of 14 Vietnamese health professionals evaluated the validity of the HOME FAST translation and rated the clarity and cultural relevance of each item. Ratings were evaluated using the content validity index (CVI). Reliability in ratings of the HOME FAST was evaluated using intra-class correlations (ICC), and ratings took place within the homes of two older Vietnamese people by six assessors. Results: In all, 22 out of 25 Vietnamese HOME FAST items were considered to have met content validity standards using the CVI. The ICC for home visit one was 0.94 (95% CI 0.87-0.97) and for home visit two was ICC 0.95 (95% CI 0.91-0.98) indicating high reliability. Discussion and conclusion: Bathroom items showed the most inconsistency in ratings indicating cultural differences in bathing activities. Descriptors of HOME FAST items will be reviewed for use in Vietnam to account for cultural and environmental differences. A larger pilot study is planned with older people living in the community in Vietnam to include calendar ascertainment of falls to determine if home hazards are associated with falling.